Impact of Social Protection Programs on West Kalimantan Poverty Amid COVID-19 Pandemic - Asian, Novelia; Pratomo, Yulius (Jurnal Ekonomi Pembangunan, 2025)
The purpose of the study was to determine how much influence Direct Cash Assistance (BLT) and the Family Hope Program (PKH) have on the poverty rate in West Kalimantan Province during the COVID-19 pandemic. This study uses panel data regression analysis with the help of the EViews application. The results of the study show that the BLT variable has a significant negative and statistically significant effect on the poverty rate in West Kalimantan Province. Each 1% increase in BLT causes a decrease in the poverty rate by 0.021% Meanwhile, the PKH variable does not have a statistically significant effect on the poverty rate in West Kalimantan Province. The findings of this study escalate the importance of increasing social protection in the form of BLT, especially during times of crisis, to help reduce poverty rates.